2023
DOI: 10.3390/ijms242216206
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profile in Development of Glioblastoma in Relation to Healthy Individuals

Pawel Jarmuzek,
Piotr Defort,
Marcin Kot
et al.

Abstract: Cytokines play an essential role in the control of tumor cell development and multiplication. However, the available literature provides ambiguous data on the involvement of these proteins in the formation and progression of glioblastoma (GBM). This study was designed to evaluate the inflammatory profile and to investigate its potential for the identification of molecular signatures specific to GBM. Fifty patients aged 66.0 ± 10.56 years with newly diagnosed high-grade gliomas and 40 healthy individuals aged 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…There is a concurrent rise in NLR observed alongside elevated levels of 50-700 bp cfDNA in glioma patients, which suggests that tumour-associated inflammation appears to be the major contributor to the release of cfDNA into the bloodstream. The results of the receiver operating characteristic (ROC) curves analysis of NLR and SII were >0.8, indicating a potential diagnostic value for clinical prognosis for patients with high-grade glioma (Figure 1A,D), as was the case in our earlier observations [27]. The optimal threshold values corresponded to 2.295 for NLR (AUC = 0.873, specificity 80%, sensitivity 90%, RR = 4.889, 95%CI 0.782-0.963), 3.310 for LMR (AUC = 0.679, specificity 67.5%, sensitivity 65%, RR = 1.976, 95%CI 0.554-0.804), 142 for PLR (AUC = 0.581, specificity 52.5%, sensitivity 72.5%, RR = 1.658, 95%CI 0.444-0.718), and 482 for SII (AUC = 0.809, specificity 72.5%, sensitivity 85%, RR = 3.390, 95%CI 0.705-0.913) (Figure 1A-D).…”
Section: Study White Blood Cell Count-derived Inflammation Indicessupporting
confidence: 70%
See 1 more Smart Citation
“…There is a concurrent rise in NLR observed alongside elevated levels of 50-700 bp cfDNA in glioma patients, which suggests that tumour-associated inflammation appears to be the major contributor to the release of cfDNA into the bloodstream. The results of the receiver operating characteristic (ROC) curves analysis of NLR and SII were >0.8, indicating a potential diagnostic value for clinical prognosis for patients with high-grade glioma (Figure 1A,D), as was the case in our earlier observations [27]. The optimal threshold values corresponded to 2.295 for NLR (AUC = 0.873, specificity 80%, sensitivity 90%, RR = 4.889, 95%CI 0.782-0.963), 3.310 for LMR (AUC = 0.679, specificity 67.5%, sensitivity 65%, RR = 1.976, 95%CI 0.554-0.804), 142 for PLR (AUC = 0.581, specificity 52.5%, sensitivity 72.5%, RR = 1.658, 95%CI 0.444-0.718), and 482 for SII (AUC = 0.809, specificity 72.5%, sensitivity 85%, RR = 3.390, 95%CI 0.705-0.913) (Figure 1A-D).…”
Section: Study White Blood Cell Count-derived Inflammation Indicessupporting
confidence: 70%
“…The neutrophilia inhibits the immune system response by suppressing the cytolytic activity of cytotoxic T cells and natural killer cells, which is expressed in changes in the neutrophil-to-lymphocyte ratio [32]. NLR, as an effective prognostic marker in GBM patients, was demonstrated in our recently reported retrospective study and meta-analysis [1,27]. The Cox model analysis showed that an NLR ≥ 4.56 significantly increased the risk of death in GBM.…”
Section: Discussionmentioning
confidence: 95%
“…Cytokines like IL-6 and IL-8 have been identified as a part of the molecular signature of cytokines secreted by GBM tumors 64,65 . Yet so far, literature surrounding IL-8 in cancer has focused on its role in neutrophil recruitment 66 and angiogenesis 67 during tissue remodeling and inflammation 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is potential for IFN-α to re-emerge as a CML treatment as a combination therapy with TKI to lower the chance of relapse or resistance of TKI during CML therapy. In glioblastoma multiforme, the cytokine profile is used as an important indicator to determine glioblastoma progression, as a short burst of inflammatory cytokines can suppress tumor progression, yet on the other hand, chronic inflammation leads to lower immune ability against glioblastoma [109]. In addition, pro-inflammatory cytokines IL-1β, IL-6, IL-8, and IL-10 and anti-inflammatory cytokines TNFα and HMGB1 are shown to play roles in the interaction of neutrophil and glioma cells [109].…”
Section: Cytokinesmentioning
confidence: 99%